Non-Precious Metal Catalysts for C–H Borylation Enabled by Metal–Metal Cooperativity - Mankad, Neal P. (Synlett, 2014)
Homogeneous catalysts for C–H functionalization typically require precious metals such as Pd, Ru, Rh, or Ir because of their facility in mediating two-electron redox mechanisms. Base metals such as Cu or Fe instead tend to undergo one-electron redox processes. By coupling together two base metal sites in a heterobimetallic catalyst design, base metal catalysts for photochemical C–H borylation were discovered. The optimal catalyst, (IPr)Cu–FeCp(CO)2, represents the first homogeneous catalyst for C–H borylation that contains no precious metals. Using metal–metal cooperativity in this way allows for base metal catalysts to replace precious metal catalysts while maintaining advantageous regioselectivity patterns. The proposed mechanism for heterobimetallic C–H borylation features bimetallic versions of classic organometallic reaction steps, serves as a guide for future catalyst designs, and opens the possibility for other precious metal transformations to be approached using metal–metal cooperativity as a design strategy.
Keywords: boron; carbene complexes; copper; homogeneous catalysis; iron